Breast cancer screening in young women - Ya. I. Kochetkova; O. P. Krashenkov (ABV-press, 2023)
Breast cancer is the main cause of cancer death in women under the age of 40. However, the organized mammographic screening of a young healthy woman was recognized by most experts as ineffective. This article is a brief overview about understanding of the risks of developing breast cancer in young women and a possible personalized screening in this group of patients.